2016
DOI: 10.1080/10916466.2016.1174715
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the asphaltene deposition along the flow of the oil in tubing: Experimental study and a parametric analysis

Abstract: In this work, a novel experimental setup was designed and utilized to carry out the n-alkane induced asphaltenes for understanding the kinetics of deposition and also effects of oil velocity, oil-precipitant volumetric dilution ratio, and temperature on the rate of asphaltene deposition. As the deposited layer of asphaltenes makes it difficult for the flow of oil along the tube, measurement of the pressure drop across the tube section of setup enabled the measurement of the amount and extent of deposition proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…They also observed that increasing the flow velocity and decreasing the tubing surface temperature decreases the deposition rate significantly. a novel experimental flow loop setup was designed by Khorram et al [6] and constructed to carry out the turbulent flow of oil (Re up to ≈ 7500) through continuous measurements of pressure drop across the pipe. Their results showed that flow rate and asphaltene concentration are two most important factors in the rate of asphaltene deposition and decreasing them cause the attachment of asphaltene particles to the surface are decreased.…”
Section: Pipe-circularmentioning
confidence: 99%
See 1 more Smart Citation
“…They also observed that increasing the flow velocity and decreasing the tubing surface temperature decreases the deposition rate significantly. a novel experimental flow loop setup was designed by Khorram et al [6] and constructed to carry out the turbulent flow of oil (Re up to ≈ 7500) through continuous measurements of pressure drop across the pipe. Their results showed that flow rate and asphaltene concentration are two most important factors in the rate of asphaltene deposition and decreasing them cause the attachment of asphaltene particles to the surface are decreased.…”
Section: Pipe-circularmentioning
confidence: 99%
“…Also they have highest molecular weight and most polar oil components [1,2]. Asphaltenes composition, structure and stability are dependent on its source, and the type of solvent used for the extraction of oil [3][4][5][6][7][8][9][10][11]. Formation of asphaltene deposition during petroleum production causes several operational issues such as total or partial blocking of pipeline and wellbore, changes in wettability and some damages in equipment [12].…”
Section: Introductionmentioning
confidence: 99%